HUBUNGAN KETERSEDIAAN DAN TATA LETAK SAFETY SIGN TERHADAP PENGETAHUAN PENUMPANG TENTANG KESELAMATAN PELAYARAN DI KMP X - Laila Ariniawati; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Shipping safety is being priority and indicators of success that need to be considered by a shipping service provider company. Good communication and coordination between regulators, operators, service providers and passengers is needed to realize the safety of shipping. The X Passenger Motor Ship makes safety sign as one of the communication media to convey safety information. Safety sign must be understood by everyone, especially passengers who are aboard the ship in order to realize the safety of shipping. The purpose of this study was to analyze the relationship between the availability and layout of safety signs on passenger knowledge about cruise safety in the X Passenger Motor Ship. The type of research used was quantitative with cross-sectional study approach. The instrument used was a questionnaire which was realized in the form of a google form. The sample in this study was passengers of the X Passenger Motor Ship with inclusion and exclusion criteria. The results of the study using the chi-square test showed that there was a relationship between the availability of safety sign (p-value = 0.013; α = 0.05) and the safety sign layout (p-value = 0.007; α = 0.05). The X Passenger Motor Ship was recommended to use 2 languages in the installation of safety signs and to re-check the installation of the safety sign as a whole according to the needs and the potential danger so that the sign can be seen and read clearly by passengers so that the delivery of safety information is easily accepted and understood by passengers.